A community based study on dengue awareness and preventive practices among urban slum population in Hyderabad, South India - Varma, Pavani; Mohandas, Anu; Pattnaik, Snigdha; N., Balakrishna; G., Kumar Kranthi (International Journal of Research in Medical Sciences, 2021)
Background: Dengue is identified as public health problem due to its rapid spread throughout the world. In India raising trend of dengue cases in monsoon is being observed. Objectives were to determine the level of awareness regarding dengue fever and practice of preventive measures and its association with socio-demographic factors; and to find out the association between awareness and practice of preventive measures. Methods: A community based cross sectional study was conducted among 150 residents of urban slum area, Shaikpet. Mean scores of awareness and practices were found and with a cut off >60% categorized as good. Chi-square test was used to find association with socio-demographic factors. Logistic regression was done for risk estimation. Results: The awareness regarding dengue fever was only 22.7% with a mean score, 8.1 (SD=3.74). Good practices were shown by 55.3% with a mean score of 10.7 (SD=5). Among those who were aware majority belonged to higher educational level (p=0.048). A significant difference was observed between income and occupation with practices. A positive correlation was found between awareness and practices in dengue fever (r=0.511, p<0.001). Females (OR=2.5) and school level education (OR=3.4) were predictors of poor awareness while professionals and low income were predictors of poor practices (p<0.05). Conclusions: Better aware people were found to practice preventive measures. So, grass root level workers can provide health education among households focusing on behaviour change, regarding preventive measures. Appropriate use of information, education and communication through mass media and social network will be beneficial.